2023
DOI: 10.1101/2023.02.07.527438
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessing vector competence of mosquitoes from northeastern France to West Nile virus and Usutu virus

Abstract: West Nile virus (WNV) and Usutu virus (USUV) are two arthropod-borne viruses that circulate in mainland France. Assessing vector competence has only been conducted so far with mosquitoes from southern France while an increasingly active circulation of WNV and USUV has been reported in the last years. The main vectors are mosquitoes of the Culex genus and the common mosquito Culex pipiens. Here, we measure the vector competence of five mosquito species (Aedes rusticus, Aedes albopictus, Anopheles plumbeus, Cule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 44 publications
1
2
0
Order By: Relevance
“…The viral RNA copies quantified in the mosquitoes in this study are consistent with other reports that measured viral loads in Culex pipiens pipiens infected with WNV (48,67) and USUV (67). There was no significant difference in Culex pipiens pipiens body titers between USUV EU and USUV AF, but only USUV AF was able to disseminate to the head, wings, and legs.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The viral RNA copies quantified in the mosquitoes in this study are consistent with other reports that measured viral loads in Culex pipiens pipiens infected with WNV (48,67) and USUV (67). There was no significant difference in Culex pipiens pipiens body titers between USUV EU and USUV AF, but only USUV AF was able to disseminate to the head, wings, and legs.…”
Section: Discussionsupporting
confidence: 90%
“…A field study on French Culex pipiens s.l. also observed a low infection rate for USUV EU lineage 3 (1.4%) while infection was much higher for WNV lineage 1 (38.7%) (48). Furthermore, a study on American Culex pipiens pipiens found that they were unable to transmit USUV (a Netherlands 2016 isolate) (49).…”
Section: Discussionmentioning
confidence: 97%
“…In addition, the detection of WNV in Ae. albopictus echoes recent findings that this urban and anthropophilic mosquito species is able to transmit WNV and USUV under experimental conditions 38 . Unlike Culex mosquitoes, this invasive species has been reported to have strict mammalian orientated feeding preferences 39 and an avian component is a prerequisite for amplification of these viruses prior to infection of mosquitoes.…”
Section: Discussionsupporting
confidence: 86%
“…1 B, C) [ 55 ]. The drop in IR observed over time is less expected, but not unique to this study [ [56] , [57] , [58] , [59] , [60] ]. It has been suggested that observations of decreasing IRs could be due to mortality in infected mosquitoes or that mosquitoes could clear the virus at later time points [ 60 ].…”
Section: Discussionmentioning
confidence: 65%